Three Novel C-Repeat Binding Factor Genes of Dimocarpus longan Regulate Cold Stress Response in Arabidopsis - Yang, Xiaoyan; Wang, Rui; Jing, Haohao; Chen, Qiuyu; Bao, Xiuli; Zhao, Jietang; Hu, Guibing; Liu, Chengming; Fu, Jiaxin (Frontiers in Plant Science, 2020)
Longan (Dimocarpus longan) is a typical southern subtropical fruit tree species that is sensitive to cold stress. C-repeat binding factors (CBFs), as transcription factors, are crucial components involved in the molecular regulation of the plant response to cold stress. However, the role of CBF homologs in the cold response regulation of longan remains largely unknown. Here, three novel CBF genes, DlCBF1, DlCBF2, and DlCBF3, were cloned from longan. DlCBF1 and DlCBF2 contain an AP2 domain and PKKPAGR and DSAWR CBF signature motifs, while DlCBF3 has mutations within these conserved signature motifs. DlCBF1/2/3 were mainly localized in the nucleus and specifically bound to CRT/DRE cis-elements, resulting in strong transcriptional activation. DlCBF1/2 exhibited tissue expression specificity, and their expression was induced by low temperature, while DlCBF3 had no tissue specificity and barely responded to low temperature. DlCBF1, DlCBF2, and DlCBF3 overexpression in Arabidopsis-enhanced cold tolerance by increasing proline accumulation and reducing reactive oxygen species (ROS) content, accompanied by upregulated expression of cold-responsive genes (AtRD29A, AtCOR15A, AtCOR47, and AtKIN1) in the CBF cold stress response signaling pathway. In conclusion, the biological functions of DlCBF1/2/3 were somewhat conserved, but slow expression of DlCBF1/2 and low expression of DlCBF3 may partly cause the cold sensitivity of longan. Collectively, these results indicated that differences exist in the expression and function of CBF orthologs in the cold-sensitive plant species longan, and these findings may help to improve the understanding of the cold response regulation mechanism and provide important theoretical support for cold-tolerant breeding of longan.